Neonatal sepsis: Risk factors, clinical and bacteriological profile, and antibiotic sensitivity - Sethi, Anitha B; Srigade, Vedavyasa; Dharmateja, Guntur (Indian Journal of Child Health, 2018)
Background: Neonatal sepsis (NS) is a cause of very high morbidity and mortality. Reviews of bacterial spectrum and antimicrobial susceptibility help to treat NS and to develop strategies to lower neonatal mortality. Objectives: The objectives were to study organisms causing NS, their antimicrobial susceptibility pattern, predisposing factors of NS, and the presentations of NS. Methods: This prospective study was done for 1 year from August 2016 to July 2017 at a tertiary care hospital, Hyderabad with C-reactive protein (CRP), aerobic blood cultures, and sensitivities in 300 neonates with clinical sepsis. Risk factors for NS and clinical features were recorded. Significances for sex, gestational age, birth weight, and age of onset of sepsis differences were assessed. Results: Male to female ratio was 1.65:1, 39% were preterm, 40% were <2500 g in weight, and 54% had sepsis in <72 h (early onset sepsis - EOS) (p<0.05). Prolonged labor and rupture of membranes, maternal fever within 2 weeks, foul-smelling liquor, birth asphyxia, and iatrogenic factors were the risk factors in decreasing order of frequency. Refusal to feed was the most common presentation. CRP showed good sensitivity and negative predictive value while 117 (39%) cases were blood culture positive. Organisms in decreasing order of frequency were Klebsiella pneumoniae, coagulase-negative staphylococci, enterococcus, Staphylococcus aureus, Pseudomonas aeruginosa, Acinetobacter, Escherichia coli, and Group-B streptococci. Gram-negative isolates (44%) were sensitive to meropenem, amikacin, and piperacillin-tazobactam while Gram-positive isolates (56%) were sensitive to vancomycin and netilmicin and both were least sensitive to cefotaxime and ampicillin. Conclusion: Obstetric and neonatal care practices around birth need to be reviewed as EOS proportion in India is very high. Most of the isolates were resistant to cefotaxime and ampicillin, underscoring the need for the addition of penicillinase inhibitors. Timely review of antibiotics is necessary in view of widespread resistance. Focus on prevention of NS and the improvement of health systems to effectively manage it is very much needed in India.